The Effects of ESG on Firm Performance and Firm Value: A Study of Indonesian and Malaysian Listed Companies - Rasyad, Rafi Kennaufal; Afgani, Kurnia Fajar; Ali, Qaisar (Journal Integration of Management Studies, 2024)
The effect of ESG on firm value and financial performance of a company is a well-researched and controversial topic in academic research, as many authors conclude different results in their studies. Previous studies suggest that ESG has a positive effect on firm value or financial performance, while some studies suggest the opposite, while some studies also suggest that only specific factors within ESG such as environmental, social, and governance factors significantly affect firm value and financial performance of a company. To contribute to current literature in the field and to resolve the dispute in controversial results, this study aims to assess the significance of ESG on firm value and financial performance of Indonesian and/or Malaysian public-listed companies, to deduce whether ESG has positive or negative effect of firm value and financial performance, and to determine which individual factors of ESG has the most affect to the overall ESG score of each Indonesian and/or Malaysian public-listed companies. As there has been limited research on the topic in Indonesia and Malaysia, the author uses PLS-SEM to analyze the effects of ESG scores on firm value and financial performance of 10 Indonesian public-listed companies and 15 Malaysian public-listed companies using available financial and ESG scoring data from YahooFinance during the 3rd quarter of the 2022 year. The study done using PLS-SEM suggests that ESG has a significant positive effect on financial performance (proxied using ROA or Return of Assets) while ESG has no significant but positive effect on firm value (proxied using Tobin’s Q value). In addition, factor analysis of the PLS-SEM model shows that from three pillars of ESG, only social and governance scores have a correlation with the overall ESG score.